The conspecific avoidance strategies of adult female-calf humpback whales. (27th May 2021) - Indeck, Katherine L; Noad, Michael J; Dunlop, Rebecca A
Abstract: During migration, humpback whale ( Megaptera novaeangliae ) adult females and their calves use acoustic calling to help maintain contact. The signals produced by these pairs, however, may unintentionally attract nearby breeding males, which can result in interactions that have negative physical and physiological effects on the calf. Therefore, maternal females must choose the vocal and/or behavioral strategy that most effectively balances intra-pair communication with male avoidance. Here, we analyzed differences in adult female-calf vocal activity and movement behavior according to the presence of, and distance to, singing whales and other groups likely to contain males. The results of this study found that these pairs make only minimal changes to their vocal behavior in response to nearby males, suggesting that they have instead evolved calls that are naturally difficult to detect (i.e., produced at significantly lower rates and acoustic levels than other whale groups, resulting in a restricted active space). In addition, they maintain spatial separation from nearby groups by moving to shallower, inshore waters, increasing their proportion of time spent near the surface, and favoring a direct migratory course. This combination of cryptic strategies balances avoidance of unwanted conspecific interaction with the necessity of continued contact between maternal female humpback whales and their calves. Abstract : For new mothers in the animal kingdom, male aggression can be costly to them and their offspring. Those that rely heavily on acoustics must balance vocal contact with their young with the risk of being overheard by nearby animals. In humpback whales, maternal females and their calves have evolved a male avoidance strategy that combines "whispered" calling with social distancing, allowing these pairs to communicate amongst themselves while minimizing potentially harmful interactions with other whales.